2019
DOI: 10.3892/ol.2019.10038
|View full text |Cite
|
Sign up to set email alerts
|

miR‑140‑3p inhibits breast cancer proliferation and migration by directly regulating the expression of tripartite motif 28

Abstract: The present study aimed to determine the expression profile and significance of microRNA-140-3p (miR-140-3p) in breast cancer (BC). miR-140-3p expression in BC tumor tissues and cell lines was measured by reverse transcription-quantitative polymerase chain reaction. Luciferase activity reporter assay and western blotting were used to assess the effect of miR-140-3p expression on tripartite motif 28 (TRIM28). Cell growth, migration, and invasion were assessed by Cell Counting Kit-8 assay, wound-healing assay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…On the basis of the prediction from bioinformatic tools and the data from luciferase reporter, RIP and RNA pull-down assays, miR-140-3p was confirmed as a direct target of circNTRK2. MiR-140-3p was previously demonstrated as a tumor-suppressor in some types of human malignancies, such as squamous cell lung cancer [ 24 ], breast cancer [ 25 ], hepatocellular carcinoma [ 26 ] and cervical cancer [ 27 ]. In the present study, miR-140-3p expression was down-regulated in ESCC tissues and cells, and was inversely correlated to circNTRK2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the prediction from bioinformatic tools and the data from luciferase reporter, RIP and RNA pull-down assays, miR-140-3p was confirmed as a direct target of circNTRK2. MiR-140-3p was previously demonstrated as a tumor-suppressor in some types of human malignancies, such as squamous cell lung cancer [ 24 ], breast cancer [ 25 ], hepatocellular carcinoma [ 26 ] and cervical cancer [ 27 ]. In the present study, miR-140-3p expression was down-regulated in ESCC tissues and cells, and was inversely correlated to circNTRK2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…miR-140-3p enhances the sensitivity of LUAD cells to cisplatin. miR-140-3p has been reported to serve as a key tumor suppressor in several types of malignancies, where patients with lower miR-140-3p expression levels had poor prognoses (28)(29)(30)(31)33). Therefore, the present study hypothesized that upregulated miR-140-3p expression may be beneficial for the treatment of patients with LUAD.…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 88%
“…In addition, miR-708-5p has been revealed to suppress stem cell-like phenotypes in lung cancer by repressing the Wnt/β-catenin signaling pathway (26). Previous studies have suggested that upregulated miR-140-3p expression was significantly associated with reduced cell proliferation, invasion, migration and sorafenib resistance in a variety of tumors (27)(28)(29)(30). It was also reported previously that miR-140-3p expression was downregulated in lung squamous cell carcinoma (LUSC) (31), where it has been demonstrated to function as a tumor suppressor (32).…”
Section: Introductionmentioning
confidence: 99%
“…Miles et al pointed out that miR-140-3p level was reduced in ovarian cancer tumor specimens [24]. Besides, miR-140-3p was reported to be downregulated in BC, and miR-140-3p restoration could restrain BC cell growth and migration through regulating TRIM28 [15]. Consistent with these results, we demonstrated that the abundance of miR-140-3p was decreased in BC cells and tissues, and low level of miR-140-3p was closely related to advanced tumor stage.…”
Section: Accepted Articlementioning
confidence: 99%
“…MiRNAs are a class of ncRNAs (~ 22 nucleotides) that negatively modulate the expression of target genes via directly binding to the 3'UTR of target mRNAs, and miRNAs were reported as key regulators in multiple cancers [12,13]. Previous reports have shown that miR-140-3p usually serves as a tumor-suppressive miRNA in some cancers, including BC [14,15]. Nevertheless, the association between circ_0008039 and miR-140-3p in BC remains unclear.…”
Section: Introductionmentioning
confidence: 99%